Metabolic syndrome and benign prostatic enlargement: a systematic review and meta‐analysis. (16th August 2014) - Gacci, Mauro; Corona, Giovanni; Vignozzi, Linda; Salvi, Matteo; Serni, Sergio; De Nunzio, Cosimo; Tubaro, Andrea; Oelke, Matthias; Carini, Marco; Maggi, Mario
<x xml:space="preserve">Abstract</x> Objective To summarise and meta‐analyse current literature on metabolic syndrome (MetS) and benign prostatic enlargement (BPE), focusing on all the components of MetS and their relationship with prostate volume, transitional zone volume, prostate‐specific antigen and urinary symptoms, as evidence suggests an association between MetS and lower urinary tract symptoms (LUTS) due to BPE. Methods An extensive PubMed and Scopus search was performed including the following keywords: 'metabolic syndrome', 'diabetes', 'hypertension', 'obesity' and 'dyslipidaemia' combined with 'lower urinary tract symptoms', 'benign prostatic enlargement', 'benign prostatic hyperplasia' and 'prostate'. Results Of the retrieved articles, 82 were selected for detailed evaluation, and eight were included in this review. The eight studies enrolled 5403 patients, of which 1426 (26.4%) had MetS defined according to current classification. Patients with MetS had significantly higher total prostate volume when compared with those without MetS (+1.8 mL, 95% confidence interval [CI] 0.74–2.87; P < 0.001). Conversely, there were no differences between patients with or without MetS for International Prostate Symptom Score total or LUTS subdomain scores. Meta‐regression analysis showed that differences in total prostate volume were significantly higher in older (adjusted r = 0.09; P = 0.02), obese patients (adjusted r = 0.26; P < 0.005) and low serum high‐density lipoprotein cholesterol concentrations (adjusted r = −0.33; P < 0.001). Conclusions Our results underline the exacerbating role of MetS‐induced metabolic derangements in the development of BPE. Obese, dyslipidaemic, and aged men have a higher risk of having MetS as a determinant of their prostate enlargement.